1996
DOI: 10.1161/01.res.78.6.990
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rapamycin on Ryanodine Receptor/Ca 2+ -Release Channels From Cardiac Muscle

Abstract: Ryanodine receptors (RyRs) are intracellular channels that regulate the release of Ca2+ from the endoplasmic reticulum of many cell types. The RyRs are physically associated with FK506-binding proteins (FKBPs); immunophilins, with cis-trans peptidyl-prolyl isomerase activity. FKBP12 copurifies with RyR1 (skeletal isoform) and modulates its gating. A different form of FKBP with a slightly higher molecular weight copurifies with RyR2 (cardiac isoform). Previous studies have demonstrated that FKBP stablizes gatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
129
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 170 publications
(143 citation statements)
references
References 57 publications
11
129
0
3
Order By: Relevance
“…We have previously shown that calstabin-2 stabilizes the RyR2 channel in the closed state (16,22) and that PKA phosphorylation of RyR2 at Ser-2808 (Ser-2809 in humans) causes dissociation of calstabin-2 from the channel complex (7,22). Compared with RyR2 channels from sham-operated mice, RyR2 were significantly PKA-hyperphosphorylated in mice with MI ( Fig.…”
Section: Increased Calstabin-2 Binding To Ryr2 In Hearts Of Jtv519-trmentioning
confidence: 90%
See 3 more Smart Citations
“…We have previously shown that calstabin-2 stabilizes the RyR2 channel in the closed state (16,22) and that PKA phosphorylation of RyR2 at Ser-2808 (Ser-2809 in humans) causes dissociation of calstabin-2 from the channel complex (7,22). Compared with RyR2 channels from sham-operated mice, RyR2 were significantly PKA-hyperphosphorylated in mice with MI ( Fig.…”
Section: Increased Calstabin-2 Binding To Ryr2 In Hearts Of Jtv519-trmentioning
confidence: 90%
“…RyR1 or RyR2 was phosphorylated with PKA catalytic subunit (40 units; Sigma) in the presence or absence of the PKA inhibitor PKI [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] in phosphorylation buffer (8 mM MgCl 2 ͞10 mM EGTA͞50 mM Tris͞Pipes, pH 6.8). 35 S-labeled calstabin-1 or calstabin-2 were generated by using the TNT Quick Coupled Transcription͞Translation system from Promega (19).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 In the absence of FKBP12/ 12.6, a homotetrameric RyR1 or RyR2 channel can be examined in planar lipid bilayers but reveals subconductance states, consistent with a defect in coordinated activity of the four subunits that form the RyR channel. 12,13 The addition of FKBP12 to recombinant RyR1 stabilizes the channel complex, resulting in channels with full conductance. 12 These stabilizing effects are reversed by treating the channels with rapamycin or FK506 to remove FKBP12/12.6 from the RyR channels.…”
mentioning
confidence: 99%